Responding to the education reform agenda: A study of school superintendents' instructional leadership. - Bredeson, Paul V.; Kose, Brad W. (Education Policy Analysis Archives, 2007)
Education reforms have affected schools and the educators who work in them. Using state-wide survey data from 1993 and 2003, this study examines how the work of school superintendents has been affected over a ten-year period by these reform initiatives, especially increased demands for accountability. The general message from our data is that superintendents are interested in curriculum and instruction and believe these are important tasks, but the daily realities of their work often subvert even the most committed professional. Further, the data indicate that superintendents may be able to use external accountability mechanisms as levers to move the internal accountability systems to support improved teaching and learning.